pls.... give me the right solution of this Question
![](https://hi-static.z-dn.net/files/d7f/ea173435b3bb7f091997ab9f514e136c.jpg)
Answers
p =
p =
p = (3 + 2 + 2√6)
p² = (5 + 2√6)²
p² = (25 + 24 + 20√6)
p² = (49 + 20√6)--------------( 1 )
similarly,
q =
q =
q = (3 + 2 - 2√6)
q = (5 - 2√6)
q² = (25 + 49 - 20√6)
q² = (49 - 20√6)-------------( 2 )
adding-----------( 1 ) & ------------( 2 )
p² + q² = (49 + 20√6) + (49 - 20√6)
p² + q² = 49 + 49
hence, the value of p² + q² = 98
Answer:
98
Step-by-step explanation:
Consider the given question. First taking
P = √3 + √2 / √3 - √2
Rationalizing the denominator we have
P = √3 + √2 / √3 - √2 x √3 + √2 / √3 + √2
here by using the formula (a^2 - b^2) = (a + b)(a - b)
Now we get (√3 + √2 )^2 / 3 - 2
P = (√3 + √2 )^2
here using the formula (a+ b)^2 = a^2 + 2ab + b^2
P = 3 + 2√6 + 2
P = 5 + 2√6
Similarly we can take up for q also.
Q = √3 - √2 / √3 + √2
Rationalizing the denominator we get
Q = √3 - √2 / √3 + √2 x √3 - √2 / √3 - √2
Q = (√3 - √2)^2 / 3 - 2
Q = (√3 - √2 )^2
here by using the formula (a - b)^2 = a^2 - 2ab + b^2
Q = 3 - 2√6 + 2
Q = 5 - 2√6
They have asked to find P^2 + Q^2
So P ^2 + Q^2 = (5 + 2√6)^2 + (5 - 2√6)^2
Since we know the formula for (a + b)^2 and (a - b)^2 . Applying it we get
25 + 20√6 + 24 + 25 - 20√6 + 24
50 + 48 = 98